ANALISIS KELAYAKAN USAHATANI BAYAM (Amaranthus Spp) DI KELURAHAN LANDASAN ULIN UTARA KECAMATAN LIANGANGGANG KOTA BANJARBARU - Irvani Rama Saputra (Fakultas Pertanian UVAYA Banjarmasin, 2019)
The purpose of this research was to know the profit, the explicit cost, the implicit cost and feasibility analysis of spinach superior variety farming business